Basic Developmental Characteristics of the Fall Armyworm, Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae), Reared under Laboratory Conditions - Dinah Marri; Samuel Adjei Mensah; Daniel Ashie Kotey; John Abraham; Maxwell Kelvin Billah; Michael Osae (Psyche: A Journal of Entomology)
The life cycle of the invasive alien insect pest, fall armyworm (FAW), Spodoptera frugiperda (J.E. Smith), was studied using a colony established from field-collected larvae. Eggs, neonate larvae, and newly emerged adult moths were used in experiments to investigate the basic biology of the FAW. Adult females laid up to 1184 eggs with a mean of 469 ± 22 eggs per female. The incubation period of eggs and percentage hatchability were 2-3 days and 80–87%, respectively. The mean larval lengths from the first to the sixth instar were 4.63, 6.60, 9.76, 15.86, 25.13, and 27.81 mm, respectively. The mean larval weights were 0.003, 0.019, 0.045, 0.050, 0.060, and 0.067 g, respectively, for the six instars. The mean width of the head capsule of the sixth instar larva was 2.76 mm. The total larval duration throughout the six instar stages was 16–18 days, while the mean pupal weight was 0.25 ± 0.001 g and 0.35 ± 0.011 g for males and females, respectively. The mean pupal length was 14.3 ± 0.16 mm for males and 17.2 ± 0.14 mm for females. Pupal duration ranged from 8 to 14 days, with a mean of 10.35 ± 0.26 days, while the pupal emergence rate ranged from 60 to 94%, with a mean of 80.25 ± 1.28%. The life cycle of males lasted 33–44 days and that of females lasted 36–49 days under laboratory conditions. Adult copulation occurred between 8 and 11 pm, with the peak occurring at 9 pm. This study provides baseline information about the biology of the FAW. Apart from being an important reference point for future research on the FAW, the data provided would aid FAW management decision-making.